Enhancement of soluble CD4-mediated HIV neutralization and gp 120 binding by CD4 autoantibodies and monoclonal antibodies. - Moore, J; Sattentau, Q; Clapham, P (1990)
We have identified 6 sera containing autoantibodies to CD4 in 174 human immunodeficiency virus-type (HIV-1) positive sera tested in an antigen-capture enzyme-linked immunosorbent assay (ELISA) using sCD4, and none in 34 HIV type 2 sera. These autoantibodies do not bind to cellular CD4, but react with sCD4 to increase its binding in ELISA to monoclonal antibodies and the HIV surface glycoprotein gp120. The effect of CD4 autoantibodies is mimicked by monoclonal antibodies to the third and fourth domains of CD4. The enhanced sCD4 binding to gp120 in ELISA is reflected by a reduction in the concentration of sCD4 required to neutralize HIV-1 and HIV-2 infection in tissue culture when CD4 autoantibodies or the relevant monoclonal antibodies were present.